Factors influencing customers’ revisit intention on online booking platforms: a case study on TripAdvisor / Nurul Nazatul Maisuri Nasarrudin ... [et al.] - Nasarrudin, Nurul Nazatul Maisuri; Mashuri, Mas Affandy; Abu Bakar, Redhuan; Zaeimoedin, Teku Zariff; Bibit, Nur Syahira; Johari, Noorsa Riza (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
The expansion of the Internet has made it possible for people to connect as customers via online platforms where they may exchange material and affect each other's purchasing decisions. This study aims to determine factors that influence customers’ revisit intention on an online booking platform, TripAdvisor.com. The approach is quantitative, employing a questionnaire to gather information from people who read hotel reviews online before making a reservation. The non-probability sampling techniques were used and only 119 respondents participated in answering the questionnaire. Before that, a pilot test consisting of 30 respondents participated in answering the questionnaire. Using IBM SPSS Version 27 to analyze the data, it was possible to determine how online reviews, website interactivity, website security, and privacy have influenced customers’ revisit intention. The practical implications of this paper are that online travel agencies can use the identified factors, such as online reviews, website interactivity, safety, and privacy, to improve their services and retain customers. By providing a great online review system, an interactive website, and ensuring safety and privacy, online travel agencies can increase customers' revisit intention. This can lead to increased revenue and customer loyalty. Additionally, the study highlights the importance of TripAdvisor.com and other similar websites in influencing customers' revisit intention. The results of this study can help online travel agencies to understand the factors that influence customers' revisit intention and take necessary steps to improve their services.